Impact of Chronic Exposure to Two Neonicotinoids on Honey Bee Antennal Responses to Flower Volatiles and Pheromonal Compounds - Favaro, Riccardo; Roved, Jacob; Haase, Albrecht; Angeli, Sergio (Frontiers in Insect Science, 2022)
Volatile compounds provide important olfactory cues for honey bees (Apis mellifera L.), which are essential for their ecology, behaviour, and social communication. In the external environment bees locate food sources by the use of floral scents, while inside the hive, pheromones such as the queen mandibular pheromone (QMP) and alarm pheromones serve important functions in regulating colony life and inducing aggressive responses against intruders and parasites. Widely reported alterations of various behaviours in- and outside the hive following exposure to pesticides could therefore be associated with a disturbance of odour sensitivity. In the present study, we tested the effects of neonicotinoid pesticides at field concentrations on the ability of honey bees to perceive volatiles at the very periphery of the olfactory system. Bee colonies were subjected to treatments during the summer with either Imidacloprid or Thiacloprid at sublethal concentrations. Antennal responses to apple (Malus domestica L.) flower volatiles were studied by GC-coupled electro-antennographic detection (GC-EAD), and a range of volatiles, a substitute of the QMP, and the alarm pheromone 2-heptanone were tested by electroantennography (EAG). Short-term and long-term effects of the neonicotinoid treatments were investigated on bees collected in the autumn and again in the following spring. Treatment with Thiacloprid induced changes in antennal responses to specific flower VOCs, with differing short- and long-term effects. In the short term, increased antennal responses were observed for benzyl-alcohol and 1-hexanol, which are common flower volatiles but also constituents of the honey bee sting gland secretions. The treatment with Thiacloprid also affected antennal responses to the QMP and the mandibular alarm pheromone 2-heptanone. In the short term, a faster signal degeneration of the response signal to the positive control citral was recorded in the antennae of bees exposed to Thiacloprid or Imidacloprid. Finally, we observed season-related differences in the antennal responses to multiple VOCs. Altogether, our results suggest that volatile-specific alterations of antennal responses may contribute to explaining several behavioural changes previously observed in neonicotinoid-exposed bees. Treatment effects were generally more prominent in the short term, suggesting that adverse effects of neonicotinoid exposure may not persist across generations.